E-Wallet: Sistem Pembayaran Dengan Prinsip Hifzul Maal - Rohmatun Ni'mah; Indah Yuliana (Universitas Siliwangi, 2020)
Millennials, the development of technology and information have an impact on various systems are no exception to the payment system. Especially in the payment system, technological advances are able to shift the role of cash and electronics wallet (e-wallet) emerged as a payment instrument capable of making payment processes faster, easier, efficient, and safer. Although it has many benefits and advantages, the suitability of e-wallet with maqashid syariah in hifzul maal still needs to be discussed. Conformity with the sharia maqashid is very important to determine whether the e-wallet is in accordance with hifzul maal or not. The method used in this study is a qualitative method with the type of library research. From the results of the study, it was generally obtained e-wallet was in accordance with maqashid syariah. This suitability is obtained by fulfilling the principle of preserving wealth and benefit. However, e-wallet is considered not in accordance with hifzul maal because this e-wallet is still prone to technological crime, and waste can occur because one person can have more than one e-wallet account.